(untitled) (El Hilo de la Fabula, 2023)
This text, Hablar en nuestra propia lengua como un extranjero (Speaking one’s own language as a foreigner), is an online conference that the author gave on May 11th, 2023, at the Facultad de Humanidades y Ciencias FHUC-UNL 4 during the cycle: Escrituras y lecturas migrantes. Italia, España y Argentina en contacto, and is part of the book, soon to be published in Argentina, La gelosia delle lingue, (My Language Is a Jealous Lover, ed. Rutgers University Press, 2023). This is a self-translation the author made of his own text, combining parts of the prologue and other chapters, in which the problem of language change is analyzed using Dante’s De vulgari eloquentia.